Perspective taking in language: integrating the spatial and action domains - Beveridge, Madeleine E.; Pickering, Martin J. (Frontiers in Human Neuroscience, 2013)
Language is an inherently social behaviour. In this paper, we bring together two research areas that typically occupy distinct sections of the literature: perspective taking in spatial language (whether people represent a scene from their own or a different spatial perspective), and perspective taking in action language (the extent to which they simulate an action as though they were performing that action). First, we note that vocabulary is used inconsistently across the spatial and action domains, and propose a more transparent vocabulary that will allow researchers to integrate action- and spatial-perspective taking. Second, we note that embodied theories of language comprehension often make the narrow assumption that understanding action descriptions involves adopting the perspective of an agent carrying out that action. We argue that comprehenders can adopt embodied action-perspectives other than that of the agent, including those of the patient or an observer. Third, we review evidence showing that perspective taking in spatial language is a flexible process. We argue that the flexibility of spatial-perspective taking provides a means for conversation partners engaged in dialogue to maximise similarity between their situation models. These situation models can then be used as the basis for action language simulations, in which language users adopt a particular action-perspective.